Helminthiasis and Hygiene Conditions of Schools in Ikenne, Ogun State, Nigeria - Ekpo, Uwem Friday; Odoemene, Simon Nnayere; Mafiana, Chiedu Felix; Sam-Wobo, Sammy Olufemi (PLOS Neglected Tropical Diseases, 2008)
BackgroundA study of the helminth infection status of primary-school children and the hygiene condition of schools in Ikenne Local Government Area of Ogun State, Nigeria was undertaken between November 2004 and February 2005 to help guide the development of a school-based health programme.Methods and FindingsThree primary schools were randomly selected: two government-owned schools (one urban and the other rural) and one urban private school. No rural private schools existed to survey. A total of 257 schoolchildren aged 4–15 y, of whom 146 (56.8%) were boys and 111 (43.2%) were girls, took part in the survey. A child survey form, which included columns for name, age, sex, and class level, was used in concert with examination of stool samples for eggs of intestinal helminths. A school survey form was used to assess the conditions of water supply, condition of latrines, presence of soap for handwashing, and presence of garbage around the school compound. The demographic data showed that the number of schoolchildren gradually decreased as their ages increased in all three schools. The sex ratio was proportional in the urban school until primary level 3, after which the number of female pupils gradually decreased, whereas in the private school, sexes were proportionally distributed even in higher classes. The prevalence of helminth infection was 54.9% of schoolchildren in the urban government school, 63.5% in the rural government school, and 28.4% in the urban private school. Ascaris lumbricoides was the most prevalent species, followed by Trichuris trichiura, Taenia species, and hookworm in the three schools. Prevalence of infection in the government-owned schools was significantly higher than in the private school (χ2 = 18.85, df = 2, p<0.0005). A survey of hygiene conditions in the three schools indicated that in the two government schools tapwater was unavailable, sanitation of latrines was poor, handwashing soap was unavailable, and garbage was present around school compounds. In the private school, in contrast, all hygiene indices were satisfactory.ConclusionsThese results indicate that burden of parasite infections and poor sanitary conditions are of greater public health importance in government-owned schools than in privately owned schools. School health programmes in government-owned schools, including deworming, health education, and improvement of hygiene conditions are recommended.